Muscle fatigue induced by two different resistances: Elastic tubing versus weight machines - Melchiorri, G.; Rainoldi, A. (Journal of Electromyography and Kinesiology, 2011)
Elastic tubes are devices relatively inexpensive, easy to use, portable and safe, which are claimed to provide advantages with respect to training with free weights or weight machine. The aim of this work was to assess neuromuscular modification induced by the use of two different muscle contraction modalities (elastic versus weight resistances) until exhaustion. Fourteen healthy physically active male students (age: 28 ± 6 years; body mass 72.1 ± 11.0 kg; height: 173.5 ± 6.9 cm) were recruited. They were requested to reach exhaustion with dynamic contraction at 70% of their own One Repetition Maximal (1RM) using, in two different days and in random order, Thera Band® tubes or traditional weight plates on an arm machine designed and built for those tasks. Before and after such contractions a standardized fatiguing isometric test (3 Maximal Voluntary Contractions, MVC plus 60 s at 60% MVC) was requested to assess differences induced by the exhaustion sessions. During fatiguing tests surface EMG signals were recorded from biceps brachii muscle with linear arrays of eight electrodes (silver bars 10 mm apart, 5 mm long, and 1 mm diameter) in single differential configuration. Initial values and rates of change of Average Rectified Value (ARV), MeaN power Frequency (MNF) and muscle fiber Conduction Velocity (CV) were calculated to compare the effects of the two contraction modalities. No differences were found between "elastic session" and "weight session" PRE MVCs (31.9 ± 8.8 and 29.9 ± 8.3 nm, respectively) and endurance times (28 ± 6 and 26 ± 7 s, respectively). The same was observed for POST values. During the post-contraction isometric fatigue test, the only parameters influenced by the contraction modality were the initial CV and the rate of change in CV which were 12% and 37% greater (p < 0.05) respectively after contractions performed with elastic resistance compared to free weights. These findings confirm others for which contractions done with the use of elastic band seem to require greater muscle activation; moreover, they highlight a sort of "muscle conditioning" after that specific contraction modality which requires the use of faster motor units. It is thus possible to consider the practical use of such elastic devices to increase the neuromuscular activation, for instance in specific rehabilitation settings where slow movements with minimal risk of injury are requested (post surgery rehabilitation, physical activity with elderly people or children).